The dogs of Venice : a novel - Rowley, Steven, 1971- (G.P. Putnam's Sons, 2025)
"After months of planning a romantic holiday getaway in Venice, Paul is blindsided when his five-year marriage suddenly unravels. Fueled by heartbreak, Paul endeavors to take the trip alone. Soon after arriving in Italy, he notices a small, scruffy, self-assured dog trotting alongside a canal with the confidence he so desperately wants for himself. When their paths cross again, Paul feels compelled to learn how his new four-legged friend thrives on his own. Amid the food, sights, and welcoming people of Venice, Paul's journey culminates in a magical encounter that leads him to feel real connection-to a dog, to a foreign city and, most importantly, to himself. Capturing Steven Rowley's signature wit, insight, and indelible characters, The Dogs of Venice offers another timeless story of love lost, and independence found-a holiday tonic for the soul"--